Becoming kin : an indigenous call to unforgetting the past and reimagining our future - Krawec, Patty (Broadleaf Books, 2022)
"Weaving her own story with the story of her ancestors and with the broader themes of creation, replacement, and disappearance, Krawec helps readers see settler colonialism through the eyes of an Indigenous writer. Settler colonialism tried to force us into one particular way of living, but the old ways of kinship can help us imagine a different future. Krawec asks, What would it look like to remember that we are all related? How might we become better relatives to the land, to one another, and to Indigenous movements for solidarity? Braiding together historical, scientific, and cultural analysis, Indigenous ways of knowing, and the vivid threads of communal memory, Krawec crafts a stunning, forceful call to 'unforget' our history."--Book jacket flap.